-9(z-1)=-8z-4

Simple and best practice solution for -9(z-1)=-8z-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(z-1)=-8z-4 equation:


Simplifying
-9(z + -1) = -8z + -4

Reorder the terms:
-9(-1 + z) = -8z + -4
(-1 * -9 + z * -9) = -8z + -4
(9 + -9z) = -8z + -4

Reorder the terms:
9 + -9z = -4 + -8z

Solving
9 + -9z = -4 + -8z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '8z' to each side of the equation.
9 + -9z + 8z = -4 + -8z + 8z

Combine like terms: -9z + 8z = -1z
9 + -1z = -4 + -8z + 8z

Combine like terms: -8z + 8z = 0
9 + -1z = -4 + 0
9 + -1z = -4

Add '-9' to each side of the equation.
9 + -9 + -1z = -4 + -9

Combine like terms: 9 + -9 = 0
0 + -1z = -4 + -9
-1z = -4 + -9

Combine like terms: -4 + -9 = -13
-1z = -13

Divide each side by '-1'.
z = 13

Simplifying
z = 13

See similar equations:

| 15+16x= | | 28+3y=28 | | .91(8000-y)+.97y=7800 | | 15x+16=x | | n*2-23=0 | | -l-19l-1-23-2= | | -19l-l-23-2= | | 5y^2-16+11=0 | | -4(-6)+y=29 | | -91=9t+8 | | 7x^3-x^2-112x+16=0 | | x+(x*.15)=27.6 | | 5(8c-1)-12=38c+5 | | .50(10x-2)=4 | | 34-52(12n-34)+235=32+101(35n-1) | | x^3+2x=110 | | 26a+26b= | | 15s^2+32s-7=0 | | 146-3x=33x+18 | | 11-9x=175-37x | | 0.0625x^2-0.125x=1 | | x^2-2x+1=8 | | 18x-(2x-8)=40 | | 37-3x=6x+27 | | 68-4x=8x-20 | | 7-8x=127-29x | | -10=-5(t-8) | | 7-8x=127-39x | | z^2-15=0 | | 3(x+7m+5)= | | 3x-12=4x-12 | | 50(x)=-0.4x^2+80x-1600 |

Equations solver categories